2022
DOI: 10.1002/trc2.12317
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic evaluation of verubecestat on disease‐ and symptom‐modifying effects in 5XFAD mice

Abstract: Introduction Alzheimer's disease (AD) is the most common form of dementia. Beta‐secretase (BACE) inhibitors have been proposed as potential therapeutic interventions; however, initiating treatment once disease has significantly progressed has failed to effectively stop or treat disease. Whether BACE inhibition may have efficacy when administered prophylactically in the early stages of AD has been under‐investigated. The present studies aimed to evaluate prophylactic treatment of the BACE inhibitor verubecestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In addition, to validate the pipeline, 22 VER and LEV were selected for screening based on their scores and were evaluated through the PTC pipeline. Importantly, consistent with its inhibition of BACE1, VER showed reductions in amyloid via 18F‐AV45 PET/MRI and dose dependent changes across 38 genes studied, but did not show alterations in 18F‐FDG PET/MRI or behavior measures with 3 months of prophylactic treatment starting in 3 months old 5XFAD mice 19 . Similarly LEV, a synaptic vesicle 2A antagonist (SV2A), showed significant dose and sex dependent changes in 18F‐FDG PET/MRI uptake, and differential gene expression which aligned to accelerating medicines partnership for AD (AMP‐AD) consensus clusters B (immune) and C (neuronal system).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…In addition, to validate the pipeline, 22 VER and LEV were selected for screening based on their scores and were evaluated through the PTC pipeline. Importantly, consistent with its inhibition of BACE1, VER showed reductions in amyloid via 18F‐AV45 PET/MRI and dose dependent changes across 38 genes studied, but did not show alterations in 18F‐FDG PET/MRI or behavior measures with 3 months of prophylactic treatment starting in 3 months old 5XFAD mice 19 . Similarly LEV, a synaptic vesicle 2A antagonist (SV2A), showed significant dose and sex dependent changes in 18F‐FDG PET/MRI uptake, and differential gene expression which aligned to accelerating medicines partnership for AD (AMP‐AD) consensus clusters B (immune) and C (neuronal system).…”
Section: Introductionmentioning
confidence: 59%
“…Importantly, consistent with its inhibition of BACE1, VER showed reductions in amyloid via 18F-AV45 PET/MRI and dose dependent changes across 38 genes studied, but did not show alterations in 18F-FDG PET/MRI or behavior measures with 3 months of prophylactic treatment starting in 3 months old 5XFAD mice. 19 in 5XFAD mice. 20 Combined, these studies recapitulate the clinical findings and side-effect profiles and help to validate the PTC pipeline and the STOP-AD drug selection process.…”
Section: Approachmentioning
confidence: 94%
See 2 more Smart Citations
“…Verubecestat is a beta-secretase (BACE) inhibitor that dose-dependently inhibits the production of Aβ in 5XFAD mice. In the original analyses of these open field data, verubecestat did not alter total distance moved in the open field [23] . A one-way ANOVA (F(4,160) = 4.943) on intrasession habituation data revealed that 5XFAD mice treated with vehicle or the low dose (10 mg/kg/day) of verubecestat had significantly increased activity change ratios (p = 0.0014 and 0.0235, respectively), while 5XFAD mice treated with the high dose (100 mg/kg/day) of verubecestat had reduced activity change ratios compared to vehicle-treated 5XFAD mice (p = 0.0467) ( Fig.…”
Section: Resultsmentioning
confidence: 88%